'Species' from two different butterfly genera combined into one: description of a new genus of Euptychiina (Nymphalidae: Satyrinae) with unusually variable wing pattern - Freitas AVL; Barbosa EP; Willmott KR; Wahlberg N; Lamas G (SOC BRASILEIRA ENTOMOLOGIA, 2022)
Sepona Freitas and Barbosa, gen. nov. is proposed for the Neotropical satyrine butterfly species Euptychia punctata Weymer, 1911 and its junior subjective synonyms Euptychia griseola Weymer, 1911 and Taygetis indecisa Ribeiro, 1931. The new genus has a distinctive wing pattern and shape of the valvae in the male genitalia, the latter being a unique autapomorphy within the subtribe Euptychiina. Based on molecular data, this genus is not sister to any other single euptychiine genus, instead appearing as the sister to all remaining genera in the Taygetis clade. The present paper illustrates the complexity of the taxonomy of Euptychiina, and the importance of using different sources of evidence in taxonomic studies. (C) 2016 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda.